The continuing debate on death penalty: an exposition of international, Malaysian and the shari'ah perspective - Ab Aziz, Shamrahayu (International Islamic University Malaysia, 2015)
The debate on the death penalty seems endless. Some see the death penalty as a form of human rights violation, while others consider it as a means to preserve and protect the rights of others. This article provides an exposition of the death penalty from the international, Malaysian and Shari‛ah perspectives. In doing this, a brief philosophy of human rights is given. Many international legal instruments, provisions of the Malaysian Federal Constitution and other relevant statutes, court decisions and the Qur’anic provisions and Sunnah are used to enrich the discussion. The study finds that the international instruments do not forbid nor encourage the death penalty. Thus, the experience of each country may contribute to the status of this capital punishment; some countries are still retaining it, while some others have repealed the punishment. Be that as it may, the Islamic legal position on the punishment remains unchanged but its application may be varied to suit different times and situations.